2011
DOI: 10.1039/c1mb05060e
|View full text |Cite
|
Sign up to set email alerts
|

How many trimers? Modeling influenza virus fusion yields a minimum aggregate size of six trimers, three of which are fusogenic

Abstract: PAPER Maria Pamela Dobay et al.How many trimers? Modeling infl uenza virus fusion yields a minimum aggregate size of six trimers, three of which are fusogenic Conflicting reports in leading journals have indicated the minimum number of influenza hemagglutinin (HA) trimers required for fusion to be between one and eight. Interestingly, the data in these reports are either almost identical, or can be transformed to be directly comparable. Different statistical or phenomenological models, however, were used to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…However, whether this necessarily involves inter-HA interactions is hard to conclude from these types of experiments. A large number of studies have established that multiple HAs are needed for fusion, yet there is no consensus on the number of HAs involved [88][89][90][91][92][93]. The number found depends on the experimental technique used and the model applied.…”
Section: Membrane Sculpting and Pore Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether this necessarily involves inter-HA interactions is hard to conclude from these types of experiments. A large number of studies have established that multiple HAs are needed for fusion, yet there is no consensus on the number of HAs involved [88][89][90][91][92][93]. The number found depends on the experimental technique used and the model applied.…”
Section: Membrane Sculpting and Pore Formationmentioning
confidence: 99%
“…Single-particle experiments on influenza viral fusion showed that the waiting times between decrease of the pH and the cessation of rolling, and hemifusion and pore formation events showed rise-and-decay behavior, suggesting that these processes involve multiple steps [61,88,96,97,100]. The powerful combination of single-particle experiments and analytical [101] and numerical [61] modeling has resulted in a picture in which fusion is the result of a number of HAs acting in a parallel, stochastic fashion, whose proximity allows their stochastic activity to result in a level of coordination needed to overcome the large energetic barriers associated with fusion.…”
Section: Experimental Design Of Single-particle Viral Fusion Assaysmentioning
confidence: 99%
“…Based on the postulated aggregation of an estimated six HA molecules required for fusion (three of which have to undergo a conformational change [33]), we concluded that a cluster of HA molecules is formed whose center is not accessible to hMAbs. Accordingly, three or more HA spikes can still undergo The attached viruses were then incubated with titrated amounts of HA stem-reactive (3.1, 1.12, and FI6) or hemagglutinationinhibiting (30D1 and H36-4) MAbs, and residual infectivity was detected.…”
Section: Discussionmentioning
confidence: 99%
“…the confirmation change required for infection (33). We believe that the lower impact of prior cell attachment on the neutralizing activity of hemagglutination-inhibiting antibodies originates in the poor affinity of the HA protein for its receptor: apically binding antibodies should have no problem with displacing dissociated receptors if they are sufficiently affine and concentrated.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis showed that the discrepancy was rooted in their use and interpretation of different statistical inference methods. This led us to develop a stochastic model 9 inspired by an Algorithmic/Executable Systems Biology approach and implemented in the model checker PRISM. The model not only verified the conclusion of the Harvard group about the number of fusogenic trimers, it also provided more details about related quantities such as the aggregation size and the number of membrane-bound trimers in the minimal configuration.…”
Section: A "Viromimetic" Approach To Targeted Drug Deliverymentioning
confidence: 99%